The Student Teams Learning Model Achievement Division (Stad) Through Use Downloading Board Props Mathematics Learning Outcomes - Syah, Firman; Wahyuningsih, Eleonora Dwi; Sina, Ibnu (Program Studi Pendidikan Matematika, Universitas Pancasakti Tegal, 2023)
The direction or aim of the research is to determine the effectiveness of Student Teams Achievement Division learning through the use of derivative board teaching aids on mathematics learning outcomes. The research approach used is a quantitative approach and the research design used is a non-equivalent pretest posttest quasi-experimental design. The population of this research was class XI students at SMA N 5 Tegal City. Random sampling was taken by lottery with class XI IPA 1 students as the trial group , XI IPA 2 as the control group , and XI IPA 3 as the experimental group . In testing validity , point biserial correlation is used . For reliability testing, kr 20 is used . The prerequisite test is carried out using a normality test using the Liliefors test. Then the f test is carried out as a homogeneity test. The testing carried out resulted in 30 valid questions out of the 35 questions created. The results of research on the hypothesis obtained F count = 5.46 and F table = 3.98 so the calculated F is greater than the F table , namely 5.46 > 3.98, so it can be concluded that there is a difference in the learning outcomes of students in the STAD learning model using derivative board teaching aids and the conventional learning model.